Simulação de cenários no terceiro setor: uma aplicação em uma Fundação de Apoio à Instituição de Ensino Superior - Presrlak, Maria Inês (2016)
Scenario projection is an efficient tool to predict future events and formulate strategies to address these scenarios. The purpose of this study was to simulate scenarios for an organization of the Third Sector, a Foundation to Support Higher Education Institution, using the Red Model of scenario simulation. The Red Model consists of five steps, application of the Delphi technique, competitive intelligence, scenario simulation, strategy formulation and action plan. From a qualitative approach, the study was of the exploratory type and is characterized as a case study. The development of the study was directed by critical variables identified by a panel of six experts, made from the Delphi technique, with semi-structured interview application. The objective of the work was achieved, and as a result, there is the simulation of three scenarios and 12 strategies with their goals aligned. With the simulated scenarios, possible execution strategies were formulated, which have characteristics of improvement in the management of the Foundation (optimistic scenario); implementation of new services, reduction of costs, partnerships and cooperation policies with similar Foundations (intermediate and pessimistic scenario); and change of statutory objectives (pessimistic scenario). For each strategy formulated was elaborated a goal (fifth stage of Rojo’s Model). These goals were elaborated in line with the strategies, seeking objective actions in the implementation of the strategies, and some strategies and goals were initiated during the preparation of this study. The results of this study demonstrate that the application of the Rojo’s Model provides a broader view of the business, since its dynamics of using different sources of information (Delphi technique, strategic tools, managerial participation) allows a more critical analysis for the simulation of scenarios and formulation of strategies and goals. The study also demonstrated that scenario simulation is an efficient tool to reduce uncertainties and to elaborate an action plan applicable in the third sector, which can contribute to the growth of the sector organizations, knowledge of possible scenarios, elaboration of strategies to minimize possible negative impacts and to potentiate the positive ones, according to the simulated scenarios, and for the decision making.